2006
DOI: 10.1682/jrrd.2005.07.0122
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor training: Experiencing the changing body

Abstract: Abstract-This study examined the experiences of persons with incomplete spinal cord injury who participated in locomotor training (LT). LT is an emerging rehabilitation intervention for enhancing the recovery of walking in persons with central nervous system disorders. Multiple interviews and field observations provided data from eight participants, including four veterans. Findings indicate that experiences of bodily changes were prevalent among participants. Themes included (1) experiencing impaired or absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In acknowledging these concerns, we should note that our sample size of 11 participants was comparable to that found in previous studies of persons with iSCI [30,37]. Another limitation of the current study was the lack of diary usage to track the occurrence of sickness, physical pain, fatigue, and special occasions that may have influenced the number of steps taken by participants.…”
Section: Discussionmentioning
confidence: 69%
“…In acknowledging these concerns, we should note that our sample size of 11 participants was comparable to that found in previous studies of persons with iSCI [30,37]. Another limitation of the current study was the lack of diary usage to track the occurrence of sickness, physical pain, fatigue, and special occasions that may have influenced the number of steps taken by participants.…”
Section: Discussionmentioning
confidence: 69%
“…Another strategy to improve walking after SCI is to administer BWS treadmill training combined with functional electrical stimulation (FES). Its benefits have been noted in terms of CNS regeneration, initiation of stepping, improving foot clearance, knee extension, and strength in both acute and chronic participants [41–43]. However, a recent meta-analysis revealed that people with SCI who used FES did not significantly increase their walking speed and capacity when compared with patients who were treated with other approaches [40].…”
Section: Discussionmentioning
confidence: 99%
“…To answer this question, we entered an LT site and asked patients to interpret the meanings of the changes in their bodies. Previous studies have retrospectively examined perceptions of the changed body after iSCI (Chau et al, 2008; Edgerton et al, 1991; Hannold, Young, Rittman, & Behrman, 2006; Nymark et al, 1998; Seymour, 1998), but few have examined changes occurring during the course of the therapy. We interviewed persons with iSCI ( n = 5) three times throughout their LT to explore how they told their stories of their changing bodies across a 12-week time period.…”
mentioning
confidence: 99%